SURGICAL TREATMENT FOR METASTATIC TUMORS IN THE CHIASMAL-SELLAR REGION: A REVIEW OF LITERATURE AND ANALYSIS OF THE AUTHORS’ OBSERVATIONS - M. A. Stepanyan; P. L. Kalinin; A. N. Shkarubo; M. A. Kutin; D. L. Rotin; N. N. Grigoryeva; E. R. Vetlova (Опухоли головы и шеи, 2015)
The authors analyze their experience in treating metastases in the chiasmal-sellar region (CSR), which has been gained at the Acad. N.N. Burdenko Neurosurgery Research Institute in 2000 to 2011 (a follow-up was made in 93 patients with metastatic skull base tumors, of them 19 (20.4 %) metastases were located in CSR), as well as the data available in the literature.